PERBAIKAN BEBAN KERJA KERJANTARA DALAM KEGIATAN PENEBANGAN SECARA MEKANIS MELALUI PENERAPAN PRINSIP ERGONOMI - Soenarno Soenarno; Maman Mansyur Idris (Jurnal Penelitian Hasil Hutan, 1990)
Tree felling  operations in  Indonesia are commonly  done by  standing or bending  workers,  using chain saws.  These techniques cause  high  stump residues  (about  8.94%)  and  increase  workers' energy  consumption by 12% for standing and 55% for bending  workers' positions.From ergonomics point of  view, above techniques cause  body position to be less natural,  produce longer static muscular work,  reduce  work hours, create early fatique  and physiological effect  like work stress.This  paper described  the  effect of  improved felling method on work  stress of  chain saw  operators  and  construction wood production.  An investigation was carried out in two private forest companies in Central Kalimantan  in 1988. The results are as the following:The  improved  felling  method decreases  work  stress  of  chain  saw  operators;  showed   by the reduction  of pulse  rate to the amount  of 13-15 beats/minute.                                                                          The  improved  method  of felling  trees with  buttress  heights  of  < 50 cm and 50-150    cm cause the increase in construction  wood products  about  0.354  m3 and 0.542 m3  per  tree felled,  respectively.